2020
DOI: 10.1002/ceat.202000316
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Manifold Microchannel Heat Sinks for Thermal Management in a Li‐Ion Battery

Abstract: The microchannel heat sink is an effective technology for the thermal management of Li-ion batteries. The overall performance of two heat sinks with improved thermal management of Li-ion batteries was determined by a numerical simulation model. A manifold microchannel heat sink (MMC) and a traditional microchannel heat sink (TMC) with different aspect ratios of microchannels were developed. Thermal transfer performance and pressure drop characteristics of two heat sinks were compared by Fluent. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Moreover, our ability to reliably create multi-level hierarchical structures will allow us to aggressively scale up forced convection based active cooling device using a second 3D manifold layer for efficient fluid delivery. High performance cooler scale-up is an immensely important goal being pursued in the field of embedded cooling; this will allow us to pack energy dense power electronic components closely together and continue the trend of improving electronics speed and energy density 8 , 43 , 52 , 54 . Pan et al performed numerical simulations in ANSYS Fluent to compare Manifolded Coolers (MMC) design with Traditional 2D Coolers (TMC)s and showed that at same flow rates, the MMCs can achieve similar levels of thermal performance as the TMCs but achieve a massive 4× to 6× reduction in total device pressure and thus, 4× to 6× improvement in Coefficient of Performance (COP) 43 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our ability to reliably create multi-level hierarchical structures will allow us to aggressively scale up forced convection based active cooling device using a second 3D manifold layer for efficient fluid delivery. High performance cooler scale-up is an immensely important goal being pursued in the field of embedded cooling; this will allow us to pack energy dense power electronic components closely together and continue the trend of improving electronics speed and energy density 8 , 43 , 52 , 54 . Pan et al performed numerical simulations in ANSYS Fluent to compare Manifolded Coolers (MMC) design with Traditional 2D Coolers (TMC)s and showed that at same flow rates, the MMCs can achieve similar levels of thermal performance as the TMCs but achieve a massive 4× to 6× reduction in total device pressure and thus, 4× to 6× improvement in Coefficient of Performance (COP) 43 .…”
Section: Resultsmentioning
confidence: 99%
“…High performance cooler scale-up is an immensely important goal being pursued in the field of embedded cooling; this will allow us to pack energy dense power electronic components closely together and continue the trend of improving electronics speed and energy density 8 , 43 , 52 , 54 . Pan et al performed numerical simulations in ANSYS Fluent to compare Manifolded Coolers (MMC) design with Traditional 2D Coolers (TMC)s and showed that at same flow rates, the MMCs can achieve similar levels of thermal performance as the TMCs but achieve a massive 4× to 6× reduction in total device pressure and thus, 4× to 6× improvement in Coefficient of Performance (COP) 43 . In addition to active coolers, such hybrid, multi-height wicks will also enable scale up of heat spreader technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our ability to reliably create multi-level hierarchical structures will allow us to aggressively scale up forced convection based active cooling device using a second 3D manifold layer for efficient fluid delivery. High performance cooler scale-up is an immensely important goal being pursued in the field of embedded cooling; this will allow us to pack energy dense power electronic components closely together and continue the trend of improving electronics speed and energy density 8,43,52,54 . Pan et al performed numerical simulations in ANSYS Fluent to compare Manifolded Coolers (MMC) design with Traditional 2D Coolers (TMC)s and showed that at same flow rates, the MMCs can achieve similar levels of thermal performance as the TMCs but achieve a massive 4× to 6× reduction in total device pressure and thus, 4× to 6× improvement in Coefficient of Performance (COP) 43 .…”
Section: Improvements In Microfluidicsmentioning
confidence: 99%
“…High performance cooler scale-up is an immensely important goal being pursued in the field of embedded cooling; this will allow us to pack energy dense power electronic components closely together and continue the trend of improving electronics speed and energy density 8,43,52,54 . Pan et al performed numerical simulations in ANSYS Fluent to compare Manifolded Coolers (MMC) design with Traditional 2D Coolers (TMC)s and showed that at same flow rates, the MMCs can achieve similar levels of thermal performance as the TMCs but achieve a massive 4× to 6× reduction in total device pressure and thus, 4× to 6× improvement in Coefficient of Performance (COP) 43 . In addition to active coolers, such hybrid, multi-height wicks will also enable scale up of heat spreader technologies.…”
Section: Improvements In Microfluidicsmentioning
confidence: 99%
“…It is an adaptive exponential upwind style, which adds artificial viscosity to the original problem and reduces numerical fluctuations. This paper uses this method as the basic numerical discrete format [2]. We use the coupled Newton iteration method to solve the nonlinear equations and propose using the algebraic multigrid (AMG) preconditioning GMRES method to solve the linear equations in the Newton iteration.…”
Section: Introductionmentioning
confidence: 99%